Evaluation of ZnO-doped membranes for biofouling mitigation limitations of standard microbial tests and the need for advanced assessment - Vēvers, Ralfs (Environmental technology, 2025)
Membrane filtration is a safe and sustainable water treatment method; however, membrane fouling remains a major challenge that limits its broader application. Modified membranes for fouling mitigation have been extensively studied, including photocatalyst incorporation for organic matter degradation and biofouling control. However, no commercially available photocatalytic membranes exist to date, possibly owing to the lack of understanding of their properties. Furthermore, conventional microbiological test methods commonly used in membrane research are insufficient for accurately assessing membrane antibiofouling properties. Mixed-matrix dual-layer membranes with varying concentrations of zinc oxide nanoparticles were prepared and characterized using multiple testing approaches. Despite achieving >99.999% reduction in cultivable Escherichia coli, viability assays revealed that only half of the cells were dead, with the rest entering a viable but nonculturable (VBNC) state and forming microcolonies, resulting in misleading CFU-based results. Additionally, Pseudomonas aeruginosa biofilm formation was evaluated using fluorescence staining to assess extracellular polymeric substance (EPS) production. While P. aeruginosa survived and multiplied on the photocatalytic membranes, biofilm maturation was inhibited, with EPS protein production reduced by up to 84% compared with the unmodified reference